Desain Multimedia Based Learning Untuk Media Pembelajaran MYOB Accounting 15 - Muhammad Assiddiq; Akhmad Qashlim (LPPM Universitas Al Asyariah Mandar, 2015)
Efforts to improve the professional capabilities in learning activities in college demands the ability to take advantage of technological developments to offer the learning system using electronic media and multimedia-based learning. Multimedia learning can be applied to create an animation that explains the theories and can be applied to all the lecture material. This research will design multimedia-based learning media based learningMenggunakan two methods approaches Instructional Model Development and Model of open learning and distance education. This study focused on the design of multimedia instructional media that contains illustrations using MYOB software and not on the content of accounting and analysis of the users, Multimedia created with Macromedia Flash. Results of research such as the implementation of multimedia learning media containing the cases of accounting and this is the case then will be settled using MYOB accounting, settlement instructions and using MYOB accounting as a means of settlement of the case made in the multimedia models.